2009
DOI: 10.1152/ajplung.90516.2008
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide-dependent PP2A regulation of TNFα-induced IL-8 production in respiratory epithelial cells

Abstract: IL-8 is a key mediator in the pathophysiology of acute lung injury. TNFalpha stimulates IL-8 production in respiratory epithelial cells by activating both the NF-kappaB and MAP kinase pathways. The precise mechanism by which these pathways are downregulated to terminate IL-8 production remains unclear. We studied the regulatory role of the serine/threonine phosphatase, PP2A, on the signaling pathways involved in IL-8 production from respiratory epithelial cells. Inhibition of PP2A using okadaic acid or gene kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…One previous study demonstrated that IL-8 production was dependent on early inflammatory gene products, notably TNF>, which activated both the NF-JB and MAPK pathways. 21 Our TNF> blocking test with infliximab treatment demonstrated that infliximab inhibited IL-8 production on MOs at the mRNA and protein levels. Thus, IL-8 not only comes from TF-FVIIaYstimulated MOs but also results from TNF> stimulation from TF-FVIIaY stimulated MOs.…”
Section: Discussionmentioning
confidence: 82%
“…One previous study demonstrated that IL-8 production was dependent on early inflammatory gene products, notably TNF>, which activated both the NF-JB and MAPK pathways. 21 Our TNF> blocking test with infliximab treatment demonstrated that infliximab inhibited IL-8 production on MOs at the mRNA and protein levels. Thus, IL-8 not only comes from TF-FVIIaYstimulated MOs but also results from TNF> stimulation from TF-FVIIaY stimulated MOs.…”
Section: Discussionmentioning
confidence: 82%
“…31 PP2A can also be activated by ceramide independently of SET/I2PP2A. 33 Thus, as our data in Figure 4 argued that PP2A activity regulated autophagy and cell viability, we next determined whether PTX and SOR treatment acts to promote PP2A activation and cell killing through a ceramide-dependent pathway. Knockdown of ceramide synthase 6 (LASS6) prevented PTX and SOR from activating PP2A (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, previous studies indicated that PP2A is involved in the activation of proinflammatory signaling cascades and participates in the regulation of intricate immune responses. For instance, TNF-a activates PP2A through production of ceramide, which suppresses the JNK, p38, and ERK MAPK pathways governing the termination of cellular inflammatory activation (31,32). On the other hand, it has been reported that PP2A positively regulates the NF-kB pathway; PP2A forms a complex with IkB kinase, which is essential for proper induction of IkB kinase activity (33).…”
Section: Discussionmentioning
confidence: 99%